Analisis Multimodal Podcast Berbasis AI dalam Segmen ‘Kalo Tokoh Cerita Rakyat Boleh Curhat’ pada Akun Instagram @cantingcreative - Lintang Asmaraning Pramudhanti; Hanna Nurhaqiqi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyze meaning-making in AI-based podcast content entitled ‘Kalo Tokoh Cerita Rakyat Boleh Curhat’ on the Instagram account @cantingcreative. Using a qualitative approach, the research applies Kress and van Leeuwen’s multimodal analysis, focusing on visual, linguistic, and audio modes, supported by the theory of mediatization of culture proposed by Hjarvard and Hepp. The data consist of five episodes with the highest engagement selected from the series. The findings reveal that folklore is transformed from traditional narratives into dialogic and multimodal digital content. Folklore characters are represented in contemporary forms through visual aesthetics, conversational language, and podcast formats. The study also identifies integrated product placement within the narrative. This research concludes that AI-based podcasts represent a process of cultural mediatization, in which folklore adapts to the logic of social media and the digital economy.